IDDF2020-ABS-0061 Impact of treatment with tenofovir alafenamide (TAF) or tenofovir disoproxil fumarate (TDF) on hepatocellular carcinoma (HCC) incidence in patients with chronic hepatitis B (CHB). (18th November 2020) - Yuen Chan, Henry Lik; Lim, Young-Suk; Seto, Wai Kay; Ning, Qin; Agarwal, Kosh; Janssen, Harry LA; Pan, Calvin O; Chuang, Wan Long; Izumi, Namiki; Fung, Scott; Brunetto, Maurizia; et al.
Abstract : Background: Potent antivirals can reduce HCC incidence in CHB. TDF and TAF are first-line treatments, and in Phase 3 studies through 3 years, TAF has shown antiviral efficacy similar to TDF, higher rates of ALT normalization, and no resistance. We evaluated HCC incidence in patients participating in these ongoing studies. Methods: HBeAg-positive (n=1039) and -negative (n=593) patients with HBV DNA 20, 000 IU/mL and ALT >60 U/L (males) or >38 U/L (females) were randomized (2:1) to TAF 25 mg QD or TDF 300 mg QD for up to 3 years, followed by open-label TAF through Year 8. Patients with hepatic decompensation, co-infection with HCV/HDV/HIV, or evidence of HCC were excluded. HCC was assessed at 6 monthly intervals by hepatic ultrasonography beginning after Week 96 and by local standards of care. The standardized incidence ratio (SIR) for HCC was calculated for observed cases relative to predicted cases using the REACH-B model. Results: 1632 patients were followed for up to 4 years; HCC was seen in 16 patients (0.98%; 7 TAF; 9 TDF); median time to onset was 568 days. At baseline HCC patients were older (median age 53 vs 40 y; p<0.001), had lower median HBV DNA (6.2 vs 7.3 log10 IU/mL; p=0.041) and were more likely to have cirrhosis (FibroTest score 0.75; 31% vs 10%; p=0.004). For study patients, the overall SIR was significantly reduced with TAF or TDF treatment 0.45 (95% CI 0.278 -0.740) (table 1 ). HCC incidence was significantly reduced (SIR 0.42, 95% CI 0.23 to 0.75) in noncirrhotic patients (n=11 vs 26.5 predicted), but not for cirrhotic patients (n=5 vs 8.1 predicted). The SIR was significantly reduced in noncirrhotic patients receiving TAF (n=5), but not in those with TDF (n=6). Conclusions: In CHB patients treated with TAF or TDF for up to 4 years, HCC incidence was reduced, particularly in noncirrhotic patients. Additional follow up is needed to further characterize the impact of longer-term treatment on HCC risk reduction.